5(a-4)=6(a-7)

Simple and best practice solution for 5(a-4)=6(a-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(a-4)=6(a-7) equation:


Simplifying
5(a + -4) = 6(a + -7)

Reorder the terms:
5(-4 + a) = 6(a + -7)
(-4 * 5 + a * 5) = 6(a + -7)
(-20 + 5a) = 6(a + -7)

Reorder the terms:
-20 + 5a = 6(-7 + a)
-20 + 5a = (-7 * 6 + a * 6)
-20 + 5a = (-42 + 6a)

Solving
-20 + 5a = -42 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-20 + 5a + -6a = -42 + 6a + -6a

Combine like terms: 5a + -6a = -1a
-20 + -1a = -42 + 6a + -6a

Combine like terms: 6a + -6a = 0
-20 + -1a = -42 + 0
-20 + -1a = -42

Add '20' to each side of the equation.
-20 + 20 + -1a = -42 + 20

Combine like terms: -20 + 20 = 0
0 + -1a = -42 + 20
-1a = -42 + 20

Combine like terms: -42 + 20 = -22
-1a = -22

Divide each side by '-1'.
a = 22

Simplifying
a = 22

See similar equations:

| -[8x+(3x+8)]=1-(3x+3) | | -0.64-6.7u=-6.7u | | 8-3[5-(4y-8)]=0 | | -13+2r+2-r=1+4r | | x^5+3x^4-3x^3-x^2-3x+3=0 | | 17p-1=3p+12+14p | | 10a-45=3(a-15) | | x+92=-47 | | -4(1-4v)-6=-32+5v | | -2+4z=4z-2 | | 10a-45=3a-45 | | 2r+1=4r-1 | | x-3=-40 | | 8(c-3)=5c+24 | | 79+x=94 | | 3x-4(2x-9)=5x+11 | | w=100/4 | | -19.55-6.6j=-19.3j+17.1j+18.73 | | (-51)+x=38 | | 6x+4x=18 | | 8h-11(h+4)=-77 | | 7x+4x=-x | | 1108473/4=x | | 7(z+11)=4(z+11) | | 3X^2-20x+15=0 | | -15+16+19d=20+19d | | 12(2x-9)=4(6x+6) | | 6x-17=4x+31 | | (-87)+x=-25 | | 0=8v-8v | | 2(3k+7)+12(2+k)=-16 | | -3x+6x=-12+4x-5x |

Equations solver categories